Farmers knowledge on potential uses of rice straw: an assessment in MADA and Sekinchan, Malaysia - MZ Rosmiza, WP Davies, CR Rosniza Aznie, M Mazdi, MJ Jabil, (N/A, 2014)
Farmers knowledge on potential uses of rice straw: an assessment in MADA and Sekinchan, Malaysia by MZ Rosmiza, WP Davies, CR Rosniza Aznie, M Mazdi, MJ Jabil,